Alinhamento entre os conteúdos de contabilidade nos cursos de Ciências Contábeis no Brasil com os pronunciamentos técnicos do CPC harmonizados com as normas internacionais de contabilidade - Alves, Diego Saldo (Universidade do Vale do Rio dos Sinos, 2015)
This study aims to analyze whether the accounting content in the curricula of Accounting courses in higher education institutions in Brazil are aligned with the Technial Pronouncement CPC which origins are the international accounting standards . The research is classified as descriptive , documentary , qualitative and quantitative . The sample consists of 105 higher education institutions in Brazil that offer the Accounting course in classroom mode and publish their syllabus and/ or program content on their web sites or through e-mail by the coordinators of Accounting courses . The analysis of the data relied on tables , graphs, charts , based on descriptive statistics and also evaluation of differences in means of adherence by region, academic organization and academic category. The results showed that the average adherence of Brazilian IES in relation to CPC is 37.3 % , the average of adherence by region is between 30 % to 40%. In public and private higher education institutions the average of adherence are 37.9 % and 37.2 %, respectively. Regarding Academic Organization , the average rate of adherence of University Centers is 40.2 % , 36% in Colleges and universities 38% . Rates of CPCs adherence in relation to higher education institutions shows that the CPC 00 - The Conceptual Framework for Financial Reporting , CPC 16 - Inventories , CPC 26 - Presentation of Financial Statements , CPC 27 - Property, Plant and Equipment and CPC 30 - Revenue indices have 100%. It is concluded in this study that IESs in Brazil belonging to the sample have low adherence in relation to CPCs.
Keywords: Ensino; Alinhamento com os pronunciamentos técnicos do CPC; Normas internacionais de contabilidade; Education; Alignment with the technical pronouncements CPC; International accounting standards; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis